Peltogynoids and 2-Phenoxychromones from Peltophorum pterocarpum and Evaluation of Their Estrogenic Activity - Polasek, Johanne; Queiroz, Emerson Ferreira; Marcourt, Laurence; Meligova, Aggeliki K.; Halabalaki, Maria; Skaltsounis, Alexios-Leandros; Alexis, Michael N.; Prajogo, Bambang; Wolfender, Jean-Luc; Hostettmann, Kurt (Planta Medica, 2013)
Phytochemical investigation of the dichloromethane extract of the leaves of Peltophorum pterocarpum, a tropical ornamental tree, led to the isolation of twelve compounds (1–12). One new derivative of peltogynoid ophioglonin (1) and a new 2-phenoxychromone (2) with its 3′-O-β-D-glucoside derivative (3) are described here for the first time. In addition, nine flavonoid derivatives, including peltogynoid ophioglonin (4), were isolated for the first time from this plant. The structures were determined by spectroscopic and chemical methods. Evaluation of the estrogenic activities of 1, 2, and 4 using different model cell systems revealed that 4 was estrogenic and that 2 was largely inactive. Interestingly, 1 was unable to stimulate the proliferation of breast and endometrial cancer cells but exhibited substantial estrogen receptor α-mediated activation of gene expression. This observation indicates that 1 can be further evaluated for its cancer chemopreventive potential.
Keywords: Peltophorum pterocarpum; Fabaceae; peltogynoid; phenoxychromone; estrogenic activity